Portable LSPR Sensing Platform with Cloud-Based Data Logging for Malathion Monitoring in Agricultural Food Samples - Salleh, Muhammad Afiq; Tukiran, Zarina; Morsin, Marlia; Mahmud, Farhanahani; Tukiran, Nor Anis Intan Aqiah; Razali, Nur Liyana (Evolution in Electrical and Electronic Engineering, 2026)
Excessive use of malathion in agriculture can result in food contamination, environmental pollution, and health risks to consumers. Conventional detection methods such as High-Performance Liquid Chromatography (HPLC) and Gas Chromatography-Mass Spectrometry (GC-MS) offer high accuracy but require expensive equipment and laboratory-based analysis. This work presents a portable Localised Surface Plasmon Resonance (LSPR) sensing platform with integrated cloud-based data logging for the monitoring of malathion in agricultural food samples. The developed system combines gold nanobipyramids (GNBPs), an AS7265x spectroscopy sensor, and ESP32-enabled wireless communication to support spectral acquisition, real-time monitoring, and centralised cloud data storage. Experimental evaluations were conducted using chilli, tomato, and cabbage extracts at a resonance wavelength of 860 nm. Chilli extract showed an increase in intensity from 20.172 to 69.056, with an R² value of 0.9963, while cabbage extract increased from 63.895 to 86.507, with an R² value of 0.993, following the addition of GNBPs and malathion. In contrast, tomato extract showed a decreasing intensity trend from 106.305 to 82.379, possibly due to nanoparticle aggregation influenced by the acidic properties of the sample matrix. The obtained results demonstrated distinguishable spectral variations between pesticide-free and malathion-treated samples, indicating the feasibility of the proposed sensing platform for preliminary pesticide screening. In addition, the implemented cloud logging framework enabled real-time wireless storage of spectral datasets, improving data accessibility, traceability, and long-term record management for future agricultural monitoring applications.